Analisis Peran Media Sosial dalam Membentuk Interaksi Sosial Generasi Z - Areta Raina Yustatian; Barkah Purnama; Eka Abdillah; Ima Ima; Muhammad Agung Permana Putra; Intan Solehah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Social media has become an important part of Generation Z's life and plays a major role in shaping their social interaction patterns. This study aims to analyze the role of social media in shaping Generation Z's social interactions through a literature review of various studies and scientific journals. The results of the study indicate that Generation Z has a high level of social media usage and utilizes digital platforms as a means of communication, information seeking, entertainment, learning, and self-expression. The presence of social media has changed communication patterns to be faster, more flexible, and more interactive through the use of various digital features such as emojis, stickers, short videos, and other visual content. In addition to providing convenience in expanding social networks, building digital identities, and increasing social participation, excessive use of social media can also have negative impacts such as reduced intensity of face-to-face interactions, decreased quality of interpersonal communication, and the emergence of dependence on digital media. Therefore, digital literacy and wise use of social media are needed so that Generation Z can utilize technology optimally without reducing the quality of social relationships in real life. Thus, social media has a significant role in shaping Generation Z's social interaction patterns, both in positive and negative aspects.